2006
DOI: 10.1139/l06-052
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of corrosion on bond strength at the steel–concrete interface with finite-element analysis

Abstract: This paper examines the basic influence of corrosion on bond strength at the steel–concrete interface and the associated slip and cracking. A nonlinear finite-element model is developed to account for the effect of corrosion on deterioration of the bond. Deterioration of the mechanical interaction between the corroding reinforcing steel and the concrete is modeled with the nonlinear finite-element program ABAQUS. The contact pressure normal to the steel–concrete interface is reduced when the concrete cracks, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 4 publications
1
26
0
1
Order By: Relevance
“…Similar experimental results have been reported by Amleh et al (2006), as shown in Table 2. Most correspond to cases of severe corrosion (greater than 10% of the corrosion loss) and wide splitting cracks (greater than 3mm).…”
Section: Crack Spacing Of Corroded Rc Members In Tensionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar experimental results have been reported by Amleh et al (2006), as shown in Table 2. Most correspond to cases of severe corrosion (greater than 10% of the corrosion loss) and wide splitting cracks (greater than 3mm).…”
Section: Crack Spacing Of Corroded Rc Members In Tensionsupporting
confidence: 90%
“…This implies that the coupling effect of corrosion and shrinkage on bonding needs to be further investigated. These cases with significant shrinkage are excluded from Further analysis is carried out to simulate the experiments carried out by Amleh et al (2006). Table 4 shows the input parameters in these cases.…”
Section: Simulation Of Residual Bond Performance In Corroded Rc Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…During the propagation phase of the corrosion, the following can be observed: reduction of the cross-sectional area, loss of original shapes and disappearance of the reinforcement steel ribs [9][10][11][12]. This may also cause both a weak interface layer and finally the disengagement of the ribs [9,13,14].…”
Section: Corrosion Damage Of Reinforced Concrete Structuresmentioning
confidence: 99%